A novel Saa3-promoter reporter distinguishes inflammatory subtypes in experimental arthritis and human synovial fibroblasts. Issue 7 (7th April 2011) - Geurts, Jeroen; Vermeij, Eline A; Pohlers, Dirk; Arntz, Onno J; Kinne, Raimund W; van den Berg, Wim B; van de Loo, Fons AJ
Abstract : Objective: To evaluate the applicability of a lentiviral (LV) serum amyloid A3 ( Saa3 )-promoter luciferase (Luc) reporter for assessing inflammation in experimental arthritis, synovial fibroblasts (SF) from osteoarthritis (OA) and rheumatoid arthritis (RA) patients. Methods: In mice, synovium was transduced in vivo by cholesterol optimised LV, and two flares of acute joint inflammation were induced by injection of streptococcal cell wall (SCW) material into the knee-joint cavity. The time course of synovial inflammation was assessed using ex vivo luciferase assays, and histology. Uptake of 99m technetium (Tc) was used to assess oedema. SF (n=12) of RA and OA patients were stratified by hierarchical clustering of whole genome expression profiles. Relative Saa3 -promoter responses were determined in cytokine- or toll-like receptor (TLR)-stimulated SF subgroups. Results: In vivo, the Saa3 -promoter reporter activity was strongly upregulated at 1 and 2 days after the first and second SCW challenge. The Saa3 -promoter activities during acute inflammation correlated with Tc uptake measurements but were more sensitive and able to respond to the ongoing synovitis in the chronic phase of SCW arthritis. Molecular stratification defined two inflammatory SF subtypes, unrelated to disease classification. Relative Saa3 -promoter responses to interleukin 1β, tumour necrosis factor α and TLR4 agonist were significantly increased in OA/RA SF with a high compared to a low inflammatory profile subtype. Serum stimulation of the Saa3 -promoter reporter cell-line could distinguish between healthy and RA patients. Conclusion: The Saa3 -promoter reporter demonstrates a robust and feasible tool for assessing the course and severity of experimental arthritis and for distinguishing molecularly distinct inflammatory SF subtypes from a heterogeneous patient population.